Isolation and Characterization of a GDP/GTP Exchange Protein Specific for the Rab3 Subfamily Small G Proteins - Manabu Wada; Hiroyuki Nakanishi; Ayako Satoh; Hisanobu Hirano; Hiroshi Obaishi; Yoshiharu Matsuura; Yoshimi Takai (1997)
The Rab small G protein family, consisting of nearly 30 members, is implicated in intracellular vesicle trafficking. They cycle between the GDP-bound inactive and GTP-bound active forms, and the former is converted to the latter by the action of a GDP/GTP exchange protein (GEP). No GEP specific for each Rab family member or Rab subfamily has been isolated. Here we purified a GEP from rat brain with lipid-modified Rab3A as a substrate. The purified protein was specifically active on Rab3A, Rab3C, and Rab3D of the Rab3 subfamily. Of these subfamily members, Rab3A and Rab3C are implicated in Ca2+-dependent exocytosis, particularly in neurotransmitter release. This GEP (Rab3 GEP) was active on the lipid-modified form, but not on the lipid-unmodified form. Rab3 GEP showed a minimum molecular mass of about 200 kDa on SDS-polyacrylamide gel electrophoresis. We cloned its cDNA from a rat brain cDNA library and determined its primary structure. The isolated cDNA encoded a protein with a Mr of 177,982 and 1,602 amino acids, which showed no homology to any known protein. The recombinant protein exhibited GEP activity toward Rab3A, Rab3C, and Rab3D. Northern blot and Western blot analyses indicated that Rab3 GEP was expressed in all the rat tissues examined with the highest expression in brain. The Rab small G protein family, consisting of nearly 30 members, is implicated in intracellular vesicle trafficking. They cycle between the GDP-bound inactive and GTP-bound active forms, and the former is converted to the latter by the action of a GDP/GTP exchange protein (GEP). No GEP specific for each Rab family member or Rab subfamily has been isolated. Here we purified a GEP from rat brain with lipid-modified Rab3A as a substrate. The purified protein was specifically active on Rab3A, Rab3C, and Rab3D of the Rab3 subfamily. Of these subfamily members, Rab3A and Rab3C are implicated in Ca2+-dependent exocytosis, particularly in neurotransmitter release. This GEP (Rab3 GEP) was active on the lipid-modified form, but not on the lipid-unmodified form. Rab3 GEP showed a minimum molecular mass of about 200 kDa on SDS-polyacrylamide gel electrophoresis. We cloned its cDNA from a rat brain cDNA library and determined its primary structure. The isolated cDNA encoded a protein with a Mr of 177,982 and 1,602 amino acids, which showed no homology to any known protein. The recombinant protein exhibited GEP activity toward Rab3A, Rab3C, and Rab3D. Northern blot and Western blot analyses indicated that Rab3 GEP was expressed in all the rat tissues examined with the highest expression in brain.